Effectiveness of Vision Therapy for Binocular Single Vision Anomalies (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
AbstractBackground: Binocular single vision is the ability to maintain visual focus on an object with both eyes, resulting in a single visual image. Anomalies in this system can cause various visual symptoms and impact daily activities such as reading, driving, and using a computer. Despite the abundance of available data, there is a significant lack of clarity regarding precise definitional criteria, standardized methods for testing and diagnosis, and global prevalence studies.Aim: To report the frequency of binocular vision (BV) anomalies in symptomatic patients (e.g., blurring, headache, or eyestrain) and to evaluate the effectiveness of vision therapy (VT)Methodology: This was a retrospective observational study conducted at the B B Eye Foundation, Kolkata, India. The analysis included 45 healthy subjects, both male and female, aged 5 to 25 years. All patients underwent a comprehensive ophthalmic examination, including visual acuity, subjective/objective refraction, and assessment of accommodative and vergence facilities. A comprehensive eye examination with binocular vision (BV) evaluation was performed, followed by the application of vision therapy (VT). Statistical analysis was conducted on pre- and post-vision therapy (VT) parameters.Results: Among 45 patients’ binocular vision (BV) anomalies were found in 44 (97.7%). 35 (77.4%) had convergence insufficiency followed by fusional vergence dysfunction in 3 (6.7%), convergence excess in 3 (6.7%), divergence insufficiency in 1 (2.3%), accommodation insufficiency with convergence insufficiency in 1 (2.3%) and accommodative infacility in 1 (2.3%). Statistical analysis and data comparison were performed using the Mann-Whitney U test with SPSS v.25 statistical software. Descriptive statistics were used to interpret the results. Statistically significant differences were found in binocular vision (BV) parameters between pre- and post-vision therapy measurementsConclusion: Following vision therapy, the symptoms associated with binocular vision (BV) anomalies improved. In particular, significant improvements were noted in: accommodation insufficiency, near point of convergence, positive fusional vergence, and negative fusional vergence.